Identification of mutations in genes commonly associated with charcot-marie-tooth disease in a malaysian cohort and a survey on the malaysian perspective of rare disorders / Sarimah Samulong - Sarimah , Samulong (2016)
Charcot-Marie-Tooth (CMT) disease is the most common form of an inherited neuromuscular disorder with an incidence of 1 in 2500. CMT can be classified into demyelinating (CMT1) or axonal (CMT2) subtypes. CMT is typically diagnosed based on clinical and electrophysiological studies, together with genetic testing for mutations in genes commonly associated with CMT. Duplications of the PMP22 gene is the most common mutation in demyelinating forms of CMT1, followed by point mutations in GJB1 and MPZ. MFN2 has been reported as the most commonly associated gene in axonal forms of CMT2. We sought to determine the frequency of mutations in these genes in our Malaysian cohort. A total of 47 CMT probands comprising of demyelinating and axonal forms were screened. PMP22 duplications or deletions were assessed by the Multiplex Ligation-dependent Probe Amplification technique (MLPA), MFN2 was analysed by High Resolution Melt (HRM) analysis whilst point mutations in PMP22, GJB1, MPZ and MFN2 were assessed by PCR and direct sequencing. We found that the frequency of PMP22 duplications, although most frequent, were fewer than described in other populations, whereas mutations in GJB1 are much more frequent compared to other studies. In demyelinating forms, mutations in PMP22 and GJB1 account for 47% of the cases, while mutations in MPZ and GJB1 were found in 4% of axonal CMT. No mutations were found in 49% of the patients raising the possibility that other rare or novel genes may be involved. Two novel variants were found in GJB1, and a combination of bioinformatics analysis including protein prediction and conservation analysis indicated that these may be pathogenic. Expression vectors harbouring the mutated alleles were generated through site-directed-mutagenesis and the cellular expression of the mutant proteins was performed. One of the mutants (P174L) showed altered GJB1 localisation while the second mutation (V74M) did not show any obvious changes. As CMT is a form of a rare disorder, we also conducted a survey to determine iv the perception of the Malaysian general public on various issues concerning rare disorders. The survey looked into aspects including types of government assistance and schooling arrangements, and the stigma associated with families with rare disorders. Around two-thirds acknowledged that genetics had a role to play in these diseases and more than half would want to have genetic testing to see if their family were at risk of getting a type of rare disorder. To our knowledge, this is the first study on CMT genetics in Malaysia. For those patients who are positive for mutations, this provides useful information for the clinicians to better understand the phenotype in these patients. For those that are not genetically classified, this study provides the first important step in identifying cases that can be used for further research into the genetic etiology of CMT. Equally important, is understanding the perceptions that the general publics have about rare disorders so that better awareness campaigns can be developed to educate the public and de-stigmatise rare disorders, so that the affected individuals can become more integrated into society.